NETIQUETTE: ETIKA BERKOMUNIKASI DALAM DUNIA CYBER - Evi Vieta Lanasier (Universitas Trisakti, 2001)
The Understanding of ethics in digital communication is as important as communication ethics in conventional communication. The usance of digital communications in many ways is incrasing such as e-mail and chat. Communication through Intermet has unique characteristics, compared to other conventional communication (face to face, telephone). In digital communication, is difficult to show emotion (might cause misunderstanding). This article describes the communication ethics of the Internet which is know as Nettiquette.